NILAI-NILAI SOSIAL DAN KEAGAMAAN DALAM TRADISI MAYANGI SEBAGAI NUANSA KEARIFAN LOKAL - Andriantoro, Suferi; Umroh, Ida Latifatul; Junaidi, Mahbub (Jurnal Murid, 2024)
The mayangi tradition is also called the ruwatan sukerta tradition, which in general can be interpreted as a traditional ceremony carried out with the aim of eliminating all forms of bad luck or all forms of bad possibilities that occur to people who must be ruwat or mayangi. The objectives of this research are: (1) to find out the implementation of the mayangi tradition (2) to know the social and religious values in the mayangi tradition (3) to know the implications of the mayangi tradition in the preservation of local wisdom. The research method used by researchers in this study is a qualitative method. Where in collecting data using interview, observation and documentation methods. The results of this study are (1) the steps of implementing the mayangi tradition are as follows, preparing the conditions or offerings of mayangi, kendurian, shadow puppet shows and watering setaman flowers (2) Social values in the mayangi tradition are cooperation, compassion, responsibility and harmony of life. Religious values in the mayangi tradition are the value of faith, the value of worship and the value of akhlaq. (3) The implication of the mayangi tradition for the preservation of local wisdom is the mayangi tradition as a form of effort in preserving culture.